التدابير القانونية للحد من جرائم القاصر الإلكترونية - سليمان, بن ناصر العجاجي (University of Eloued جامعة الوادي, 2020)
بالقدر الذي يحمله تطور التقنية وشمولها لكل مناحي الحياة ، وتسارع التدفق الإلكتروني ، وانتقال المعلومة ؛ فإنه يشكل عبئاً تشريعياً على المنظم السعودي يتمثل في صعوبة ملاحقة الجرائم المستحدثة ،والتي تتزايد بزيادة البرامج الإلكترونية ، ويزيدها تعقيداً إذا كانت الجريمة مرتكبة من قبل قاصرين ، مما يستلزم تشريع تدابير قانونية تحد من جرائم القاصر الإلكترونية ، والباحث في هذه الدراسة يتناول التدابير القانونية التي اتخذها المنظم السعودي ،و التدابير الدولية للحد من جرائم القاصر الإلكترونية ، إضافة إلى التدابير المقترحة للحد من جرائم القاصر الإلكترونية ؛ سواءً في الجانب التشريعي ، أو التقني ، أو الأمني ، ثم إني أتقدم بالشكر والعرفان لجامعة القصيم ممثلة بالبحث العلمي على رعايتهم للبحث محل الدراسة . Abstract By the development of technology it has become encompassed all walks of life. And the great acceleration in electronic flow and transmission of information. These reasons constituted enactment burden on Saudi legislator . This burden is the difficulty of pursuing the new crimes , which increasing by the increasing of cyber programs. These Complexities are compounded if the criminal is a minor. Which necessitates the enactment of legal procedures to limiting the cyber crimes of minors.The researcher in this study dealt with the legal procedures taken by Saudi legislator and international procedures to limit cyber crimes by a minor. Addition to the procedures proposed to reduce cyber crimes by a minor in the enactment aspects, technical or security aspects. I extend my gratitude to Qassim University, represented by the Deanship of Scientific Research, for their support and care for the research under study.
مجلد11، عدد1
Keywords: الجرائم؛الإلكترونية؛القاصر؛التدابير؛الحد؛الأحداث; Minors; Procedures; Limiting; Minors; Electronic; Crimes